2005
DOI: 10.1890/04-1473
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Spatially Explicit, Individual-Based Model of Red-Cockaded Woodpecker Population Dynamics

Abstract: Abstract. Stochastic population models are widely used to assess extinction risk under various management scenarios, but due to the lack of independent data, such models are tested only rarely. Here we evaluate the predictive accuracy of a stochastic, spatially explicit, individual-based model of the population dynamics of the Red-cockaded Woodpecker by comparing simulated data with independent empirical data sets from two populations. We examined primary model predictions such as population size and number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Previously existing models depicting RCW population dynamics have included no information on the species response to landscape features, portraying dispersal as simple functions of distance (Letcher et al 1998, Schiegg et al 2002, Pasinelli et al 2004, Schiegg et al 2005. Our results show that RCW movement is strongly inhibited by open areas.…”
Section: Contributions To Knowledge Of Dispersal Behavior For Each Spmentioning
confidence: 76%
See 2 more Smart Citations
“…Previously existing models depicting RCW population dynamics have included no information on the species response to landscape features, portraying dispersal as simple functions of distance (Letcher et al 1998, Schiegg et al 2002, Pasinelli et al 2004, Schiegg et al 2005. Our results show that RCW movement is strongly inhibited by open areas.…”
Section: Contributions To Knowledge Of Dispersal Behavior For Each Spmentioning
confidence: 76%
“…Using radio telemetry, we confirmed that juvenile female RCWs conduct prospecting behavior with extensive forays from their natal territory before settling on a single breeding site . Previous models depicting RCW dispersal behavior have failed to account for this prospecting behavior and for long-distance dispersal events (Letcher et al 1998, Daniels and Walters 2000, Schiegg et al 2002, Pasinelli et al 2004, Schiegg et al 2005 and, thus, may provide unrealistic depiction of RCW dispersal behavior. Despite the extensive RCW monitoring and widespread fragmentation of the longleaf pine ecosystem, because dispersal behavior was poorly known before this project, connectivity has yet to be quantified for RCW populations.…”
Section: Red-cockaded Woodpeckermentioning
confidence: 99%
See 1 more Smart Citation
“…Applying the models to real landscapes to compare simulated and observed population dynamics may be especially instructive in this regard (e.g. Lindenmayer et al 2003, Schiegg et al 2005). Sensitivity analysis is also useful in directing attention to the parameters that matter most to model performance.…”
Section: How Field Biologists Can Interact With Modelers To Improve Cmentioning
confidence: 99%
“…There are two broad categories of IBMs. In demographic-based IBMs, empirically determined demographic parameters are ascribed to individual animals whose aggregate demographic responses are used to predict how the population as a whole will be affected by a change in its environment (e.g., Stephens et al 2002, Schiegg et al 2005 of such models are rare but are, in any case, essentially interpolations because they use empirically determined demographic relationships to predict population behavior in more or less the same environments from which the empirical relationships had been established in the first place (e.g., Schiegg et al 2005).…”
Section: Introductionmentioning
confidence: 99%